Analisis Good Corporate Governance terhadap Kinerja Keuangan pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di BEI Tahun 2020-2023 - Pramanaswari, A.A. Sagung Istri (JURNAL ECONOMINA, 2024)
This study aims to examine the impact of good corporate governance (GCG) on the financial performance of companies. The research utilizes secondary data from the annual reports of consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2023. The measurement indicator for good corporate governance is managerial ownership. The population of this study consists of 58 consumer goods manufacturing companies listed on the IDX from 2020-2023. From this population, a sample of 24 companies over four years was selected using purposive sampling method. Based on hypothesis testing using the partial t-test, it was concluded that good corporate governance, measured by managerial ownership, has a significant impact on financial performance, with a value of 0.012 < 0.05, and institutional ownership also significantly affects the company's financial performance, with a value of 0.000 < 0.05. Therefore, it can be concluded that good corporate governance influences the financial performance of consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023.